The Tax Elasticity of Corporate Debt : A Synthesis of Size and Variations - Mooij, Ruud A. (IMF Working Papers; Working Paper ;, 2011)
Although the empirical literature has long struggled to identify the impact of taxes on corporate financial structure, a recent boom in studies offers ample support for the debt bias of taxation. Yet, studies differ considerably in effect size and reveal an equally large variety in methodologies and specifications. This paper sheds light on this variation and assesses the systematic impact on the size of the effects. We find that, typically, a one percentage point higher tax rate increases the debt-asset ratio by between 0.17 and 0.28. Responses are increasing over time, which suggests that debt bias distortions have become more important.